Conversion of Methane to C2 Hydrocarbons and Hydrogen Using a Gliding Arc Reactor - 胡爽慧 王保伟 吕一军 闫文娟 (等离子体科学和技术：英文版, 2013)
Methane conversion has been studied using gliding arc plasma in the presence of argon.The process was conducted at atmospheric pressure and ambient temperature.The focus of this research was to develop a process of converting methane to C2 hydrocarbons and hydrogen. The main parameters,including the CH4/Ar mole ratio,the CH4 flow rate,the input voltage,and the minimum electrode gap,were varied to investigate their effects on methane conversion rate, product distribution,energy consumption,carbon deposit,and reaction stability.The specific energy requirement（SER） was used to express the energy utilization efficiency of the process and provided a practical guidance for optimizing reaction conditions for improving energy efficiency. It was found that the carbon deposition was not conducive to methane conversion,and the gliding arc plasma discharge reached a stable state twelve minutes later.Optimum conditions for methane conversion were suggested.The maximum methane conversion rate of 43.39%was obtained under the optimum conditions.Also,C2 hydrocarbons selectivity,C2 hydrocarbons yield,H2 selectivity, H2 yield and SER were 87.20%,37.83%,81.28%,35.27%,and 2.09 MJ/mol,respectively.